1999
DOI: 10.1177/136346099002004007
|View full text |Cite
|
Sign up to set email alerts
|

The Comfort of Identity

Abstract: This article is based on empirical research using video diaries to explore the performance of sexual identities in work, domestic and social spaces. The diaries allow respondents to show the clothes they wear on different occasions, and to talk about the process of performance. The article focuses on the ways in which identity as a concept functions within 'academic', 'political' and 'subcultural' discourses of sexuality, and draws on diarists' discussions of comfort and discomfort in performing their (differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
50
1
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(54 citation statements)
references
References 2 publications
(1 reference statement)
1
50
1
2
Order By: Relevance
“…These changes reflected the freedom the men experienced to be (and to express) themselves: For a few of the participants, coming out as gay or bisexual gave them the freedom to resist heteronormative constructions of masculinity and to change their gender presentations (Hutson, 2010), adorning their bodies in ways that marked them as gay. Furthermore, as the quotations from Stuart and James indicate, many spoke of feeling more comfortable in their clothes; however, this was not a physical feeling of comfort but rather a psychological one, resulting from closing the gap between their inner and outer selves (Holliday, 1999).…”
Section: The Pleasures and Dangers Of Looking Gaymentioning
confidence: 99%
See 4 more Smart Citations
“…These changes reflected the freedom the men experienced to be (and to express) themselves: For a few of the participants, coming out as gay or bisexual gave them the freedom to resist heteronormative constructions of masculinity and to change their gender presentations (Hutson, 2010), adorning their bodies in ways that marked them as gay. Furthermore, as the quotations from Stuart and James indicate, many spoke of feeling more comfortable in their clothes; however, this was not a physical feeling of comfort but rather a psychological one, resulting from closing the gap between their inner and outer selves (Holliday, 1999).…”
Section: The Pleasures and Dangers Of Looking Gaymentioning
confidence: 99%
“…Thus, 'dressing gay' afforded both a feeling of belonging and a way of managing the appearance pressures on the gay scene (Hutson, 2010;Kates, 2002;Schofield & Schmidt, 2002). Moreover, dressing gay allowed the men to secure the right kind of 'second look' from other men when out on the scene -a cruising gaze that conveyed sexual interest (and confirmed that they 'fit'), rather than a policing or disciplining gaze, that signalled a failure to 'fit' (Clarke & Turner, 2007;Holliday, 1999 Sean's response signals the importance for some of the men of looking like the men they desire (Holliday, 2001). These men discussed evaluating other men's appearance and seeking to emulate the clothing choices of the men they found most desirable, in order to be desirable to those men (Holliday, 2001 Thus, the participants learnt what was stylish and attractive by looking at other men (Clarke & Turner, 2007;Kates, 2002).…”
Section: The Pleasures and Dangers Of Looking Gaymentioning
confidence: 99%
See 3 more Smart Citations